1.7 Gbit/in.2 gray-scale continuous-phase-change femtosecond image storage - Craig, Chris (2014)
We demonstrate high-density, multi-level crystallization of a Ge2Sb2Te5 thin film using tightly focused femtosecond laser pulses. The submicron spots with 8 distinct data storage states are written on a 1.08 μm square grid. The significant change in reflectivity of every specific state of crystallized spot allows easy optical reading and identification. As a demonstration, two gray-scale images are written into the storage medium. Our results open up potential applications in ultra-fast two-dimensional parallel cognitive computing and holography.